De-radicalization through Social Media: Social Media Literacy in Countering Terrorism in Indonesia - Syamsurrijal, M; Nurmandi, Achmad; Jubba, Hasse; Hidayati, Mega; Hariyanto, Bambang (Wawasan: Jurnal Ilmiah Agama dan Sosial Budaya, 2024)
In Indonesia, the rise of radicalism in the digital age has facilitated the spread of radical movements, particularly across social media networks. Radicalism has manifested in physical violence, often resulting in significant human casualties. This research investigates how internet media influences public literacy in countering terrorism in Indonesia. This study uses discourse analysis to examine secondary data from social media content on Twitter, Instagram, and online news sources concerning counter-radicalism and anti-terrorism efforts. These data sources are selected based on the premise that Internet media is a primary communication tool for disseminating public discourse. Additionally, the National Counter Terrorism Agency (NCTA), as a governmental body, plays a critical role in combating terrorism in Indonesia. The findings reveal that social media effectively enhances public literacy on radicalism and terrorism. Moreover, NCTA's initiatives have successfully mobilised community engagement against terrorism and radicalism in the public sphere. This research demonstrates that NCTA can significantly advance de-radicalisation efforts through the strategic use of internet media. NCTA's socialisation and de-radicalisation programs serve as crucial preventive measures against terrorism in Indonesia.